A Comparative Randomised Clinical Study Between Nebulised Fentanyl and Intravenous Fentanyl For Post Operative Pain Relief (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Background and Aim: Intravenous (IV) route for fentanyl administration is very effective for postoperative pain relief, but complications such as respiratory depression, bradycardia and hypotension have limited this route. The aim of this randomised clinical trial was to compare the efficacy of nebulised fentanyl with IV fentanyl for post-operative pain relief after lower abdominal surgery. Methods:In the post-operative wards, at the time of first onset of pain( visual analogue scale- VAS score > 5) patients were randomised into two groups and either fentanyl IV 2 ìg/kg or by nebulisation of solution containing 4 ?g/kg fentanyl over 6-8 min in 120 patients divided into two groups of 60 each. Observation were made for pain relief by visual analogue scale score 0-10. Adverse effects such as respiratory depression, bradycardia and hypotension were also recorded. Statistical analysis was performed using Medcalc software version 12, 2012. (MedCalc Software, Ostend, Belgium). Results: In the nebulisation group, it was observed that the analgesic efficacy of fentanyl had little delayed onset (10 min vs. 5 min). Nebulisation with 4 ?g/kg fentanyl produced analgesia at par to 2 ?g/kg IV fentanyl with prolonged duration (90 min vs. 30 min) and with significantly less adverse effects. Conclusions:This study shows that nebulisation with 4 ìg/kg fentanyl may be used as an alternative to IV 2 ìg/kg fentanyl for adequate post-operative pain relief.Journal of Bangladesh Society of Anaesthesiologists 2014; 27(1): 27-30